2016
DOI: 10.1021/acs.jpcc.6b05951
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Modeling Study ofn-Octane,n-Nonane, andn-Decane Films on MgO(100)

Abstract: The thermodynamic properties of n-octane, nnonane, and n-decane adsorbed on the MgO(100) surface were investigated using high-resolution, volumetric adsorption isotherms in the temperature ranges of 225−295, 245−280, and 250−310 K, respectively. Two distinct molecular layers were observed in all isotherms. The heat, differential enthalpy, differential entropy, and isosteric heat of adsorption were determined. The temperature dependence of the two-dimensional compressibility was used to identify that two-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Unfortunately, no such anomalies were observed for pentane and hexane on graphite, likely because they appear at temperatures below where these measurements were made. It was possible to locate potential phase transitions in our earlier adsorption studies of pentane and hexane on MgO(100) , and hexagonal boron nitride because the binding energies were lower and hence exhibited higher equilibrium vapor pressures overall across the same temperature ranges.…”
Section: Resultssupporting
confidence: 65%
“…Unfortunately, no such anomalies were observed for pentane and hexane on graphite, likely because they appear at temperatures below where these measurements were made. It was possible to locate potential phase transitions in our earlier adsorption studies of pentane and hexane on MgO(100) , and hexagonal boron nitride because the binding energies were lower and hence exhibited higher equilibrium vapor pressures overall across the same temperature ranges.…”
Section: Resultssupporting
confidence: 65%
“…45 Molecular dynamics simulations of long-chain linear alkanes on the MgO(100) surface found that the carbon backbone is preferentially oriented parallel to the surface at low temperature but the orientational disorder and liquid-like layer appear as the temperature is increased to room temperature. 46 Also, the disjoining pressure measurements of wetting films of n-octane and n-decane on aluminum oxide showed that the films have molar volumes identical with those of the bulk liquids. 47 These studies suggest that the comparison of ΔV* with the liquid molar volume is reasonable.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Computational and experimental sum frequency generation studies of α-pinene adsorbed on silica revealed a rotationally fluidic state; the energy difference between two distinct adsorption geometries is smaller than the thermal energy at room temperature . Molecular dynamics simulations of long-chain linear alkanes on the MgO(100) surface found that the carbon backbone is preferentially oriented parallel to the surface at low temperature but the orientational disorder and liquid-like layer appear as the temperature is increased to room temperature . Also, the disjoining pressure measurements of wetting films of n -octane and n -decane on aluminum oxide showed that the films have molar volumes identical with those of the bulk liquids .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This assumption has also been proved to be unsuitable for the study of polymers of intrinsic microporosity (PIM) designed to have a rigid and contorted backbone which swells upon adsorption of carbon dioxide at high pressures . Nevertheless, nonporous solids are often considered inert, regardless of the density and polarity of the liquid. In this work, we study the effect that organic molecules of different polarity have on the structure of a crystal surface as well as the effect on the adsorbed-phase properties that results from neglecting changes in the solid structure. We focus our attention on the adsorption of small organic molecules such as ethanol (C 2 H 5 OH), toluene (C 6 H 5 –CH 3 ), and iso-octane (C 8 H 18 ), which are commonly used as solvents in the chemical industry, on hematite (α-Fe 2 O 3 ) which is often formed on the surface of iron-containing alloys , that are extensively used for the construction of equipment and mechanical structures.…”
Section: Introductionmentioning
confidence: 99%